Single Nucleotide Polymorphisms in BCO1 and CD36 Are Related to Macular Pigment Among Children (OR05-04-19). (13th June 2019) - Liu, Ruyu; Hannon, Bridget; Robinson, Katie; Raine, Lauren; Hammond, Billy; Renzi-Hammond, Lisa; Cohen, Neal; Kramer, Arthur; Hillman, Charles; Teran-Garcia, Margarita; Khan, Naiman
Abstract: Objectives: Xanthophyll carotenoids in the retina have been linked to visual and cognitive health. While genetic variations in genes related to carotenoid cleavage (e.g., beta-carotene-15, 15′-monooxygenase [ BCO1/BCMO1 ]) and xanthophyll transport (e.g., Cluster Determinant 36 [ CD36 ]) proteins have been shown to influence MPOD in adults, it is unknown whether these relationships are evident in childhood. We examined the influence of genetic variation (single nucleotide polymorphisms [SNPs]) in BCO1 and CD36 on MPOD in 7–10 year-olds ( N = 134). Methods: Macular pigment optical density (MPOD) was assessed using heterochromatic flicker photometry. DNA was extracted from saliva samples and genotyped for six tag-selected SNPs, identified by previous work among adults. Ancestry informative markers (AIMs) were genotyped to account for ethnic heterogeneity. Dietary lutein and zeaxanthin (L + Z) was assessed using 3d food records among a subsample (N = 82). Results: Minor allele frequencies of BCO1-rs7501331 (T), CD36-rs1527483 (T), CD36-rs3173798 (C) were 0.194, 0.090 and 0.213, respectively. In the partially adjusted (AIMs, age, sex, BMI %tile) models, three of the six SNPs were associated with MPOD. Carriers of the BCO1-rs7501331 T allele had significantly lower (∼18%) MPOD than the CC homozygotes ( P = 0.042). Minor allele (T) carriers of CD36-rs1527483 exhibited lower MPOD (∼23%) than CC homozygotes ( P = 0.043). CD36-rs3173798 C allele carriers had ∼32% lower MPOD than those with the TT genotype ( P < 0.001). Applying the fully adjusted models (AIMs, age, sex, BMI %tile, L + Z) among the subsample revealed that L + Z was a significant predictor of MPOD ( P = 0.04); however, CD36-rs3173798 was the only SNP associated with MPOD ( P = 0.009). Conclusions: MPOD in children is influenced by individual genetic variation. Specifically, variation in the CD36 gene, responsible for a protein involved in transport of lipids and carotenoids, was robustly associated with macular pigment in children. These findings have implications for future recommendations for dietary or supplemental approaches to improving xanthophyll status among children. Funding Sources: NIH (HD069381); Abbott Nutrition (2012-04608). iTOPP (2011-67001-30101). USDA AFRI (2015-68001-23248) and the Department of Human Development and Family Studies.